2014
DOI: 10.1186/1471-2318-14-87
|View full text |Cite
|
Sign up to set email alerts
|

The descriptive epidemiology of delirium symptoms in a large population-based cohort study: results from the Medical Research Council Cognitive Function and Ageing Study (MRC CFAS)

Abstract: BackgroundIn the general population, the epidemiological relationships between delirium and adverse outcomes are not well defined. The aims of this study were to: (1) construct an algorithm for the diagnosis of delirium using the Geriatric Mental State (GMS) examination; (2) test the criterion validity of this algorithm against mortality and dementia risk; (3) report the age-specific prevalence of delirium as determined by this algorithm.MethodsParticipant and informant data in a randomly weighted subsample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 23 publications
2
33
0
2
Order By: Relevance
“…This is consistent across different settings: after hospitalisation [6]; in those with dementia [8, 12]; in post-operative patients [13, 14]; after critical care [11]; and in community populations [10, 15]. The only population-based study showed an 8 fold increased risk of cognitive decline following an episode of delirium [10].…”
Section: Introductionmentioning
confidence: 67%
“…This is consistent across different settings: after hospitalisation [6]; in those with dementia [8, 12]; in post-operative patients [13, 14]; after critical care [11]; and in community populations [10, 15]. The only population-based study showed an 8 fold increased risk of cognitive decline following an episode of delirium [10].…”
Section: Introductionmentioning
confidence: 67%
“…41-48 The studies vary in design, including population-based approaches, retrospective analyses of outpatients such as memory clinic patients, evaluation of ICU inpatients and those undergoing elective surgery. Nonetheless, these multiple studies consistently suggest that an episode of delirium carries substantial dementia risk, as well as an altered trajectory of cognitive recovery following surgical procedures.…”
Section: Evidence Linking Delirium and Dementiamentioning
confidence: 99%
“…A range of studies have demonstrated that delirium is associated with future long-term cognitive impairment. [9-15] However, these have major methodological limitations, either: Delirium outcomes have been measured without pre-morbid baseline cognitive assessments, i.e. observed cognitive impairment at follow-up is confounded by undiagnosed pre-existing cognitive impairment ( Figure 1, top panel );[13, 16] or Delirium has been retrospectively ascertained, so detailed information on the features any delirium is lacking ( Figure 1, middle panel ).…”
Section: Introductionmentioning
confidence: 99%
“…observed cognitive impairment at follow-up is confounded by undiagnosed pre-existing cognitive impairment ( Figure 1, top panel );[13, 16] or Delirium has been retrospectively ascertained, so detailed information on the features any delirium is lacking ( Figure 1, middle panel ). [9-12, 14, 15]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation